Urban water health: A conceptual framework and assessment system - He, Jing; Li, Yunyan; Su, Jiafu; Liao, Bo (Frontiers in Ecology and Evolution, 2023)
The quantitative evaluation of urban water health (UWH) is a crucial decision-making process in water management. Healthy water not only encompasses excellent water quality and a diverse ecology but also has other characteristics, such as the amount of water resources, supply-use-drainage problems, flooding, water cycle, and so on. This study proposes a theoretical framework and an indicator system for UWH that integrates ecosystem health and water cycle health. Subsequently, considering the time scale and regional characteristics, an objective evaluation model that combined the real coding accelerated genetic algorithm (RAGA) method and the projection pursuit (PP) method was applied to calculate indicator weights and thresholds for the urban water health index (UWHI). UWHI standard thresholds were calculated as (0.04, 0.87], (0.87, 1.80], (1.80, 2.73], (2.73, 3.50], and (3.50, 4.01] corresponding to the categories of Sick, Unhealthy, Subhealthy, Healthy, and Excellent, respectively. Using Chongqing as a case study, the results showed that the UWHI increased from 1.796 to 2.668 in 2011–2020, and the health level improved from Unhealthy to Subhealthy, approaching Healthy. For each subsystem, the results indicated that the health status of the water cycle was superior to that of the water ecosystem. Finally, a detailed analysis of the changes in the indicators identified important factors affecting water health. The results of this study revealed that the main weaknesses in Chongqing were severe soil erosion, large domestic water use, high water consumption rates, and unsatisfactory water functional areas and indicated key priorities on the path to future water management.